Towards Outdoor Collaborative Mixed Reality: Lessons Learnt from a Prototype System - Numan, Nels; Lu, Ziwen; Congdon, Benjamin; Giunchi, Daniele; Rotsidis, Alexandros; Lernis, Andreas; Larmos, Kyriakos; Kourra, Tereza; Charalambous, Panayiotis; Chrysanthou, Yiorgos; Julier, Simon; Steed, Anthony (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
Most research on collaborative mixed reality (CMR) has focused on indoor spaces. In this paper, we present our ongoing work aimed at investigating the potential of CMR in outdoor spaces. These spaces present unique challenges due to their larger and more com-plex nature, particularly in terms of reconstruction, tracking, and interaction. Our prototype system utilises a photorealistic model to facilitate collaboration between remote virtual reality (VR) users and a local augmented reality (AR) user. We discuss our design considerations, lessons learnt, and areas for future work.